2004
DOI: 10.1093/jnci/djh283
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Lavage Findings in Women With Known Breast Cancer Undergoing Mastectomy

Abstract: In breasts with cancer, ductal lavage appears to have low sensitivity and high specificity for cancer detection, possibly because cancer-containing ducts fail to yield fluid or have benign or mildly atypical cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 12 publications
7
69
0
1
Order By: Relevance
“…4,5 For ducts known to harbor cancers, some are not sampled by lavage. 8 Our study demonstrated that using cellular biomarkers, especially biomarkers of malignancy-associated field defect, one could potentially overcome the sampling problem of ductal lavage. Molecular markers, which occur before altered cellular morphology, might represent a series of genetic and epigenetic alternations needed for developing cancer in epithelium at risk.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…4,5 For ducts known to harbor cancers, some are not sampled by lavage. 8 Our study demonstrated that using cellular biomarkers, especially biomarkers of malignancy-associated field defect, one could potentially overcome the sampling problem of ductal lavage. Molecular markers, which occur before altered cellular morphology, might represent a series of genetic and epigenetic alternations needed for developing cancer in epithelium at risk.…”
Section: Discussionmentioning
confidence: 82%
“…7 However, a recent study by Khan suggested the criteria should be 100 epithelial cells. 8 Our previous study of QFIA on breast fine-needle aspiration also showed 100 cells as minimum number of single cells needed for biomarker analysis. 16 Therefore, in our study, we used 10 epithelial cells as adequate criteria for cytology analysis and 100 cells for biomarker analysis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For clinical diagnosis and prediction of the development of benign lesions to malignance, currently used biomarkers primarily are histologic atypia, cytologic atypia, cell proliferation, estrogen receptor (ER) expression, estradiol and related hormones, mammographic density, and several molecular biomarkers (9). At this time, there are no "omics"-based molecular biomarker panels for predicting benign lesions to cancer.…”
Section: Prognosismentioning
confidence: 99%